Assessing emerging multinationals “Global Mindedness” profiles - Reis, Germano Glufke; Fleury, Maria Tereza Leme; Fleury, Afonso; Zambaldi, Felipe (Revista de Administração da UFSM, 2018)
Despite the relevance of developing a global mindedness (GM) in order for firms to explore global opportunities, extant literature on GM has mostly focused on developed country multinationals, overlooking its relevance to emerging country multinationals which have unique features and internationalization patterns. In addition, the studies addressing the impacts of GM on internationalization have mostly relied on the assumption of homogeneity rather than differentiation of GM among multinationals of the same country. This study addresses this theme by exploring GM diversity among Brazilian multinationals. For that purpose, a previously developed multidimensional GM scale is adapted and validated by means of a pretest and a confirmatory factor analysis with Bayesian estimators, and used as the basis for a hierarchal cluster analysis, later optimized by means of the K-means algorithm. As a result, a GM taxonomy is identified, encompassing fully globally minded, cross-culturally skilled, international market-oriented, and domestic market-oriented multinationals. To illustrate the taxonomy, four case studies involving major Brazilian multinationals are brought to the fore by means of interviews and secondary data. The configurations identified points to the need to study GM in conjunction with both institutional and economic factors in order to explain singularities of the internationalization of emerging companies and also differentiations among firms from a single emerging country.